SPaT/MAP V2X communication between traffic light and vehicles and a realization with digital twin. (March 2023) - Wágner, Tamás; Ormándi, Tamás; Tettamanti, Tamás; Varga, István
Abstract: The present paper's focus is the V2X (Vehicle-to-Everything) communication between traffic light controller and road vehicles. After a brief review on the state-of-the-art V2X communication technologies and their feasibility for practical implementation, a brief description of their potential is discussed providing a working solution for SPaT/MAP (Signal Phase and Timing and MAP as intersection geometry) standard based communication, specifically for automotive proving ground usage. The main outcome of the proposed solution is a full y flexible traffic control system applying industrial PLC while ensuring a standardized V2X protocol. As a demonstrative HiL (Hardware-in-the-Loop) example, exploiting the elements of the traffic management system at the ZalaZONE Automotive Proving Ground, a GLOSA (Green Light Optimal Speed Advisory) scenario is presented with the developed SPaT/MAP V2X communication realizing a global optimum traffic control solution. The more, the whole framework is designed in a way that it is capable of using mixed reality components for testing purposes and realizing a digital twin for traffic lights. The method of virtualization for V2X communication is introduced using a co-simulation framework of three common software tools (SUMO, Veins, and OMNeT++). Graphical abstract: Highlights: CAVs integrate wireless communication technologies also towards the traffic lights. SPaT/MAP messages are used for V2I/I2V communication based traffic light control. A prototype of V2I/I2V communication is shown for ZalaZONE Automotive Proving Ground. The SPaT/MAP based communication features mixed reality and digital twin technologies. The featured GLOSA algorithm realizes a global optimum control.